Poetic inspiration in the philosophies of Samuel Taylor Coleridge and Muhammad Iqbal - Mohd Ramli, Aimillia (2013)

(untitled)
The stress that English Romanticism lays upon a poet’s imaginative capacity as a source of poetic inspiration finds its clearest expression in the writings of its philosopher, Samuel Taylor Coleridge (1772-1834). Unlike many of his English contemporaries, his developed a philosophy of poetic inspiration that conceptualized the notion of imagination within the context of a Christian theology that was influenced both by Platonism and German Idealism. As a student and later lecturer of English Literature, the Islamic poet Muhammad Iqbal (1877-1938) had been exposed to both English Romanticism and German Idealism. Though he recognized the importance of imagination as a source of artistic creativity, Iqbal emphasised intuition as a higher form of poetic inspiration. By adapting and merging certain aspects of English Romanticism and Islamic theology, he asserted the importance of a special type of intuition, Intuition of Existence, as a form of poetic inspiration. This paper, hence, is a comparative study of English Romanticism’s emphasis on imagination and Iqbal’s notion of intuition, in order to discuss the important roles that both Christian and Islamic theologies played in these literary philosophies respectively.